THE EFFECT OF WORK SPIRIT ON EMPLOYEE PERFORMANCE IN KFC BRANCH OF SUDIRMAN PEKANBARU - Yogie Rahmat (Jurnal Apresiasi Ekonomi, 2019)
This research conducted in KFC (Kentucky Fried Chicken) Branch Sudirman Pekanbaru. This study aims to determine the effect of work morale on employee performance at the Sudirman Pekanbaru KFC with as many samples 30 employee. Based on the results of the study, it is known that there is an influence of work spirit with the regression equation Y = 23.423+ 0,464 X. Based on the results of the T test, Thitung as big 3.496 > Ttabel (2,048) with sig (0,002) < 0,05. The meaning is that the independent variable (morale) has a significant effect on the dependent variable (employee performance) on the Sudirman branch of KFC in Pekanbaru. Based on the Determination Coefficient The magnitude of the effect of work morale on the performance of employees of sudirman kota pekanbaru KFC is equal to 30,4%. While the remaining 69.6% is influenced by other variables not included in this study.